Assessing running economy during field running with changes of direction: Application to 20 m shuttle runs - Buchheit, M.; Haydar, B.; Hader, K.; Ufland, P.; Ahmaidi, S. (International Journal of Sports Physiology and Performance, 2011)
Purpose: To examine physiological responses to submaximal field running with changes of direction (COD), and to compare two approaches to assess running economy (RE) with COD, ie, during square-wave (SW) and incremental (INC) exercises. Methods: Ten male team-sport athletes performed, in straight-line or over 20 m shuttles, one maximal INC and four submaximal SW (45, 60, 75 and 90% of the velocity associated with maximal pulmonary O2 uptake [vVO2pmax]). Pulmonary (VO2p) and gastrocnemius (VO2m) O2 uptake were computed for all tests. For both running mode, RE was estimated as the O2 cost per kilogram of bodyweight, per meter of running during all SW and INC. Results: Compared with straight-line runs, shuttle runs were associated with higher VO2p (eg, 33 ± 6 vs 37 ± 5 mL O2/min/kg at 60%, P < .01) and VO2m (eg, 1.1 ± 0.5 vs 1.3 ± 0.8 mL O2/min/100/g at 60%, P = .18, Cohen`s d = 0.32). With COD, RE was impaired during SW (0.26 ± 0.02 vs 0.24 ± 0.03 mL O2/kg/m, P < .01) and INC (0.23 ± 0.04 vs 0.16 ± 0.03 mL O2/kg/m, P < .001). For both SW and INC tests, the changes in RE with COD were related to height (eg, r = .56 [90%CL, 0.01;0.85] for SW) and weekly training/competitive volume (eg, r = -0.58 [-0.86;-0.04] for SW). For both running modes, RE calculated from INC was better than that from SW (both P < .001). Conclusion: Although RE is impaired during field running with COD, team-sport players of shorter stature and/or presenting greater training/competitive volumes may present a lower RE deterioration with COD. Present results do not support the use of INC to assess RE in the field, irrespective of running mode.